PERANAN SAKSI KORBAN TINDAK PIDANA PERKOSAAN PADA TINGKAT PENYIDIKAN - Ahmad Deda Darwis (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTModernization of information technology turned out to have a positive and negative impact on society. The positive impact of course is that we will easily get information so that we can always follow the changes, both of which occur from all corners of the country to all corners of the world. Rape can occur due to various reasons, such as the vengefulness of the perpetrator of the victim, because the offender's revenge on a woman so that another woman becomes the target of his anger, the victim compensates for feeling depressed or stressed over the various problems he faces due to environmental stimuli or pornographic images and because the perpetrators desire to channel their sexual urges that they cannot hold, also because they are supported by environmental conditions and conditions as well as perpetrators and victims that allow rape. In the process of investigating criminal acts of rape, victim witnesses have a very important role. This can be seen by reports from victim witnesses to the police about the rape crimes they experienced. Legal protection against witnesses of victims of rape at the investigation level is to provide a special room at the police station when giving testimony and their identity must be kept secret. Modernization of information technology has had a positive and negative impact on the community. The positive impact of course is that we will easily get information so that we can always follow the changes, both of which occur from all corners of the country to all corners of the world. Rape can occur due to various reasons, such as the vengefulness of the perpetrator of the victim, because the offender's revenge on a woman so that another woman becomes the target of his anger, the victim compensates for feeling depressed or stressed over the various problems he faces due to environmental stimuli or pornographic images and because the perpetrators desire to channel their sexual urges that they cannot hold, also because they are supported by environmental conditions and conditions as well as perpetrators and victims that allow rape. In the process of investigating criminal acts of rape, victim witnesses have a very important role. This can be seen by reports from victim witnesses to the police about the rape crimes they experienced. Legal protection for witnesses of victims of rape at the investigation level is to provide a special room at the police station when giving a testimony and their identity must be kept confidential Keywords: Role of Victim Witnesses, Rape, Samarinda Police, Investigation